Complete chloroplast genome of Cerasus fengyangshanica (Rosaceae), a wild flowering cherry endemic to China - Xiao-Yan Wang; Ling-Juan Liu; Sheng-Long Liu; Li-Xin Ye; Xue-Kai He; Zhong-Shuai Sun (Mitochondrial DNA. Part B. Resources, 2021)
Cerasus fengyangshanica is a wild flowering cherry endemic to Mount Fengyang, China. Here, we reported the complete chloroplast (cp) genome of C. fengyangshanica (GenBank accession number: MW160272). The cp genome was 157,964 bp long, with a large single-copy region (LSC) of 85,972 bp and a small single-copy region (SSC) of 19,086 bp separated by a pair of inverted repeats (IRs) of 26,453 bp. It encodes 129 genes, including 84 protein-coding genes, 37 tRNA genes, and 8 ribosomal RNA genes. We also reconstructed the phylogeny of Prunus sensu lato using maximum likelihood (ML) method, including our data and previously reported cp genomes of related taxa. The phylogenetic analysis indicated that C. fengyangshanica is closely related with Prunus maximowiczii.